Reacting to Samuelson: Early development economics and the factor-price equalization theorem - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2019)
Paul Samuelson's famous 1948 "factor price equalization theorem" was his main contribution to international trade theory. He demonstrated conditions under which trade in goods only would lead to full equalization of the remuneration of productive factors across countries. In practice, general factor-price equalization has not been a feature of the international economy, as Samuelson acknowledged. His theorem came out when development economics was starting to emerge as a new field of research and policy, largely based on observed international income asymmetries between poor and rich countries. The paper investigates how development economists reacted mostly (but not always) critically to that theorem, with attention to the methodological issues involved and to Samuelson's own perception of the theorem's relevance.
Keywords: B20; B27; B30; 330; Samuelson; factor-price equalization; development economics; trade theory